Commentary: Role of VEGF, nitric oxide, and sympathetic neurotransmitters in the pathogenesis of tendinopathy: A review of the current evidences - Dean, B (Frontiers Media, 2017)
I read the recent systematic review which asked some interesting questions regarding the pathogenesis of tendinopathy (Vasta et al., 2016). The statement “histologic studies have demonstrated the absence of inflammatory infiltrates” is not supported by the current evidence base.